Green Product: Our Response to Environmental sustainability - Joseph, Biju (IJRDO-Journal of Applied Science, 2017)
In achieving sustainable development Green products and the consumers’ preferences for it are important. Present world realises the importance of green environment. So more and more initiatives are coming up in different parts of the world. These initiatives in production and consumption may lead to a better environment around us. The purpose of this study is to assess the awareness and attitude of consumers regarding green products and to identify the factors which act as an obstacle to green life style. To conduct the study MALAPPURAM district of Kerala State is selected. Primary and secondary data was collected from various resources. This data was analysed with suitable statistical. The analysis reveals that the people have special concern towards the environmental protection and that is why majority of the people opt for organic products. Such an attitude by the people helps the movement of sustainable development.